The impact to demographic and academic factors on metacognition and academic self-efficacy: A study on Iranian students in health sciences - Elham Raeisi; Kamal Solati; Mathias Hossain Aazami; Nastaran Shamsipour; Zohreh Sadeghian; Soleiman Ahmady (Wolters Kluwer Medknow Publications, 2020)
BACKGROUND: Metacognition and academic self-efficacy are two emerging resources in the process of learning. Basic levels of metacognition and academic self-efficacy may differ and be influenced by demographic and academic factors. This study investigated impacts of demographic and academic factors on metacognition, metacognitive skills, and academic self-efficacy in health sciences students. MATERIALS AND METHODS: A cross-sectional study was conducted among 404 participating students attending various fields of study in health sciences at Shahrekord University of Medical Sciences. Demographic and academic data were collected. Global metacognition, metacognitive skills, and academic self-efficacy scores were assessed using published or online questionnaires. Means were compared using Student's t-test, whereas intra- and intergroups' scores were compared using one-way ANOVA test. RESULTS: Global metacognition and academic self-efficacy were not impacted by demographic students' status. The gender and age impacted both knowledge and control of process- planning (favoring male gender), as well knowledge and control-of-self (disfavoring 20-30 age class) of metacognitive skills, (P < 0.05). Academic status did not influence academic self-efficacy. The school type influenced the metacognitive skill component to knowledge and control of process-regulation (disfavoring nursing school) (P < 0.05). The academic discipline impacted the global metacognition (P < 0.05) and its knowledge and control of self-component (P < 0.01). CONCLUSIONS: Demographic and academic status does impact metacognitive skills and global metacognition scores. Given the heterogeneous level to innate metacognitive skills, this study sheds lights on usefulness to screen learners' subgroups that require supplementary educational instructions to uniformly optimize metacognitive skills.